Ruthenium-Promoted Acceptorless and Oxidant-Free Lactone Synthesis in Aqueous Medium - Bhatia, Anita; Kannan, Muthukumar; Muthaiah, Senthilkumar (Synlett, 2019)
Ruthenium-catalyzed formation of lactones from diols in aqueous medium has been demonstrated. 1,3,5-Triazaphosphaadamantane (PTA) included water-soluble ruthenium complexes [RuCl2(PPh3)(2,6-Py-(CH2-PTA)2]·2Br and [RuCl2(PPh3)2(2-PyCH2PTA)]·Br in the presence of KOH were found to be efficient for the synthesis of lactones from diols. The reported synthetic protocol is green as it uses water as solvent, avoids the use of any hydrogen acceptor/oxidant, and produces hydrogen as the only side product. Mechanistic studies revealed that lactone formation involved aldehyde intermediate and followed dehydrogenative pathway.
Keywords: diol; aqueous catalysis; dehydrogenation; lactone